Adverse effects of a single dose of gentamicin in adults: a systematic review. (3rd November 2017) - Hayward, Rachel S.; Harding, Jan; Molloy, Rob; Land, Lucy; Longcroft‐Neal, Kate; Moore, David; Ross, Jonathan D. C.
Abstract : Aims: To systematically review the frequency and type of adverse events associated with a single dose of intravenous or intramuscular gentamicin in adults, for any indication, in studies where a comparator was available. Methods: A review protocol was developed and registered (PROSPERO: CRD42013003229). Studies were eligible for review if they: recruited participants aged ≥16 years; used gentamicin intramuscularly or intravenously as a single one‐off dose; compared gentamicin to another medication or placebo; and monitored adverse events. MEDLINE, EMBASE, Cochrane Library, trial registries, conference proceedings and other relevant databases were searched up to November 2016. Risk of bias was assessed on all included studies. Results: In total, 15 522 records were identified. After removal of duplicates, screening of title/abstracts for relevance and independent selection of full texts by two reviewers, 36 studies were included. Across all the included studies, 24 107 participants received a single one‐off dose of gentamicin (doses ranged from 1 mg kg –1 to 480 mg per dose). Acute kidney injury was described in 2520 participants receiving gentamicin. The large majority of cases were reversible. There were no cases of ototoxicity reported in patients receiving gentamicin. A meta‐analysis was not performed due to study heterogeneity. Conclusions: A significant number of patients saw a transient rise in creatinine after a single dose of gentamicin at doses up to 480 mg. Persistent renal impairment and other adverse events were relatively rare.